2016
DOI: 10.1007/s11682-016-9560-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain network changes and memory decline in aging

Abstract: One theory of age-related cognitive decline proposes that changes within the default mode network (DMN) of the brain impact the ability to successfully perform cognitive operations. To investigate this theory, we examined functional covariance within brain networks using regional cerebral blood flow data, measured by 15O-water PET, from 99 participants (mean baseline age 68.6 ±7.5) in the Baltimore Longitudinal Study of Aging collected over a 7.4 year period. The sample was divided in tertiles based on longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
2
10
1
1
Order By: Relevance
“…Lower ECN‐SN FC may suggest that APOE ‐ɛ4 carriers had aberrant communication between networks critical for externally oriented cognition compared to noncarriers. While we did not observe a reliable linear relationship between the cross‐sectional changes in the ECN‐SN FC and visuospatial memory performance, both networks subserve functions related to cognitive control processes that are important for carrying out cognitive tasks (Beason‐Held, Hohman, Venkatraman, An, & Resnick, ; Suri et al, ). Therefore, one possible hypothesis is that carriers have altered regulation of control processes that subsequently influence their memory performance.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Lower ECN‐SN FC may suggest that APOE ‐ɛ4 carriers had aberrant communication between networks critical for externally oriented cognition compared to noncarriers. While we did not observe a reliable linear relationship between the cross‐sectional changes in the ECN‐SN FC and visuospatial memory performance, both networks subserve functions related to cognitive control processes that are important for carrying out cognitive tasks (Beason‐Held, Hohman, Venkatraman, An, & Resnick, ; Suri et al, ). Therefore, one possible hypothesis is that carriers have altered regulation of control processes that subsequently influence their memory performance.…”
Section: Discussioncontrasting
confidence: 64%
“…4.2 | APOE-E4 was associated with lesser coupling between task-positive intrinsic connectivity networks but not within-networks across individuals Resnick, 2017;Suri et al, 2017). Therefore, one possible hypothesis is that carriers have altered regulation of control processes that subsequently influence their memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…in MDD. Meanwhile, recent studies and our previous results suggested that the changed network processes in DMN were related to the impairment of cognitive performance, and the balance in DMN, CCN and salience network processes are essential to maintain optimal cognitive function (Wu et al, 2013 ; Beason-Held et al, 2016 ). It is feasible to study the potential correlation between VMHC in DMN and cognitive dysfunction, for it provides a new perspective for understanding the role of DMN in the process of cognitive decline in LOD.…”
Section: Introductionmentioning
confidence: 83%
“…Aging is considered in some studies as one of the most prominent problems in the short and medium term for modern societies [1], demanding more support and investment in health systems. It is widely accepted that normal aging is associated with a decline in brain functions [2], disturbing, among others, executive and memory processes [3].…”
Section: Introductionmentioning
confidence: 99%